Assessing the value of topiramate in refractory status epilepticus. (May 2016) - Madžar, Dominik; Kuramatsu, Joji B.; Gerner, Stefan T.; Huttner, Hagen B.
Highlights: There were no significant differences between episodes with and without TPM. TPM was not associated with a higher chance for successful RSE termination. There was no evidence for a particular efficacy of TPM in RSE. Abstract: Purpose: The aim of this study was to assess factors associated with the use of topiramate (TPM) in refractory status epilepticus (RSE). Methods: We retrospectively reviewed RSE episodes over a 12-year period. Episodes treated with and without TPM were compared in terms of demographics, RSE characteristics, clinical course, and outcome in univariate and multivariate analyses. Subgroups defined by type of RSE were studied separately. Functional outcome was assessed with the modified Rankin Scale. Results: Among 71 episodes, 17 (23.9%) were treated with TPM and seizure control was achieved in all of these. The results of unadjusted comparisons suggested a use of TPM in younger and healthier patients who received more perseverant treatment indicated by a higher number of antiepileptic drugs applied. In multivariate analysis adjusting for RSE duration, however, these associations lost significance. Furthermore, TPM was not a predictor of successful RSE termination in neither the overall cohort, nor in the subgroup of complex-partial RSE. Conclusion: After multivariate adjustment, no significant differences were observed between episodes treated with and without TPM in baseline characteristics, treatment, and outcome. Regarding the latter, this study does therefore not yield evidence for a particular efficacy of TPM in RSE.